Implementation of Spiritual Emotional Freedom Technique (SEFT) to Reduce Academic Tension of the Students at Baldatul Mubarakah Islamic Boarding School - Iqbal, Muhammad; Salami, Salami; Rahmi, Lisa (Journal of Community Research and Service, 2023)
There is significant cause for concern regarding the number of children who experience stressful situations while attending Islamic boarding schools; thus, preventative treatment is required to avoid negative outcomes and ensure academic achievement. The purpose of this research is to demonstrate that students at Baldatul Mubarakah Islamic Boarding School can benefit from engaging in Emotional Freedom Technique (EFT) therapy to lower their levels of academic stress. This investigation is an experimental study with pre-test and post-test control groups developed for their participation. Ten students from the Islamic boarding school Baldatul Mubarakah participated in the study. Of them, five were assigned to the experimental group, and the remaining five were assigned to the control group. As a direct result of this, there was a difference between the levels of stress felt by the experimental group and the control group while they were at the Islamic boarding school. More specifically, the experimental group felt much less stress than the control group.